FORMATION OF ETHNOCULTURAL COMPETENCE OF THE FUTURE TEACHERS BY MEANS OF A FOLK ART - H.A. Bohatyrova (Освітній вимір, 2007)
This article opens ways of formation of ethnocultural competence of the future teachers during mastering symbol shaped system of products of a folk art.